1984
DOI: 10.3109/02813438409017704
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Relocation of the Aged in Nursing Homes

Abstract: In the period 1972-76 a descriptive and experimental socio-geriatric longitudinal investigation was carried out in the municipality of Odense. The aim of the experimental aspect was prevention of relocation of the aged in nursing homes. The practical work consisted in casefinding and social medical intervention by nurses experienced in geriatrics and in close contact with interdisciplinary groups. Emphasis was placed on familiarity with the structure of the social and health services, the provisions available,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…Allocation concealment was also adequate in 33 studies at low risk of bias, but unclear in 27. Two quasi-random studies were included post-hoc and were rated high risk for randomization and allocation concealment per se [23], [24], but we concluded that the methods of assignment had the desirable characteristics of randomization. One study replaced a few intervention participants and was rated high risk for sequence generation and allocation concealment [92].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Allocation concealment was also adequate in 33 studies at low risk of bias, but unclear in 27. Two quasi-random studies were included post-hoc and were rated high risk for randomization and allocation concealment per se [23], [24], but we concluded that the methods of assignment had the desirable characteristics of randomization. One study replaced a few intervention participants and was rated high risk for sequence generation and allocation concealment [92].…”
Section: Resultsmentioning
confidence: 95%
“…Thirty papers were secondary reports of a study reported in another paper; thus, 146 studies were assessed for eligibility. Post-hoc, we included two studies (both identified in the search) in which participants were assigned using quasi-random methods that approximated the characteristics of randomization as described below [23], [24]. Sixty-four studies reported in 86 citations were included in the narrative synthesis (Table S2) [23][108], but three of these did not report any outcomes that could be included in a meta-analysis [36], [68], [74].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies were conducted in Western Europe: the United Kingdom (Pathy et al 1992;Vetter, Jones, and Victor 1984), Denmark (Gunner-Svensson et al 1984;Hendriksen, Lund, and Stromgard 1984), the Netherlands (van Rossum et al 1993), Switzerland , and Italy (Bernabei et al 1998). Only two studies were conducted in the United States (Stuck et al 1995;Zimmer, Groth-Juncker, and McCusker 1985) and three studies were conducted in Canada (Dalby et al 2000;Hall et al 1992;Hebert et al 2001).…”
Section: Input: What Is the Context Of The Intervention?mentioning
confidence: 97%
“…This study introduces a gender perspective in the inhome assessment discussion. A Danish study from the 1970s showed an insignificant effect on nursing home relocations among women only (22). Studies have confirmed that women are more aware of local activities and more likely to adapt to lifestyle advice than men (5,23).…”
Section: The Interventionmentioning
confidence: 99%